Evaluation of biological production of lactic acid in a synthetic medium and in Aloe vera (L.) Burm. f. processing by-products - Gómez-Gómez, Javier Antonio; Unidad de Saneamiento y Biotecnología Ambiental - Departamento de Biología – Facultad de Ciencias - Pontificia Universidad Javeriana, POB 56710, Bogotá D.C, Colombia (2015)
This study evaluated lactic acid production through batch fermentation in a bioreactor with Thermoanaerobacter sp. strain USBA-018 and a chemically defined culture medium and with hydrolyzed pressed extract of Aloe vera peel (AHE). The strain USBA-018 fermented various sugars, but its primary end-product was L-lactic acid. Factors which influenced L- lactic acid production were pH, addition of yeast extract (YE) and manganese chloride. Under the most favorable growing conditions for the production of lactic acid, yield (Yp/s) increased from 0.66 to 0.96 g/g with a productivity (Qp) of 0.62 g.l-1.h and a maximum lactic acid concentration of 178 mM at 26 hours of fermentation. When AHE was used, 93.3 mM, or 0.175 g.h/L, was obtained. These results show the potential for transformation of sugars that strain USBA-018 offers, but additional studies are needed to find out if different strategies using AHE as carbon source can produce large enough quantities of lactic acid to allow AHE to become a low-cost alternative substrate.